The central role of the metal ion for photoactivity: Zn– vs. Ni–Mabiq. Issue 21 (4th May 2021) - Lauenstein, Raphael; Mader, Sophie L.; Derondeau, Henrieta; Esezobor, Oaikhena Z.; Block, Matthias; Römer, Armin J.; Jandl, Christian; Riedle, Eberhard; Kaila, Ville R. I.; Hauer, Jürgen; Thyrhaug, Erling; Hess, Corinna R.
Abstract : The development of earth-abundant photoredox catalysts remains a challenge. Studies of Ni- and Zn-Mabiq complexes demonstrate how the coordinating metal ion influences the photochemistry, photodynamics and reactivity of photocatalysts. Abstract : Photoredox catalysts are integral components of artificial photosystems, and have recently emerged as powerful tools for catalysing numerous organic reactions. However, the development of inexpensive and efficient earth-abundant photoredox catalysts remains a challenge. We here present the photochemical and photophysical properties of a Ni–Mabiq catalyst ([Ni II (Mabiq)]OTf (1 ); Mabiq = 2-4:6-8-bis(3, 3, 4, 4-tetramethyldihydropyrrolo)-10-15-(2, 2-biquinazolino)-[15]-1, 3, 5, 8, 10, 14-hexaene1, 3, 7, 9, 11, 14-N6 )—and of a Zn-containing analogue ([Zn II (Mabiq)OTf] (2 ))—using steady state and time resolved optical spectroscopy, time-dependent density functional theory (TDDFT) calculations, and reactivity studies. The Ni and Zn complexes exhibit similar absorption spectra, but markedly different photochemical properties. These differences arise because the excited states of 2 are ligand-localized, whereas metal-centered states account for the photoactivity of 1 . The distinct properties of the Ni and Zn complexes are manifest in their behavior in the photo-driven aza-Henry reaction and oxidative coupling of methoxybenzylamine.